Costs and Taxes in the Light of Financial Management in Companies Listed on WSE - Lyroudi, Katerina; Bolek, Monika (Journal of Finance and Financial Law, 2022)
The purpose of the article/hypothesis: The goal of this paper is to present costs and taxes as a part of financial management process in companies listed on the WSE. In the hypothesis it is expected that costs influence taxes paid by companies in a negative way due to the tax avoidance purpose attitude presented by managers, and as a result, both liquidity and debt levels are influenced. Methodology: Correlation coefficients and regression models are evaluated to find the answers for the research questions related to the relationships between tested variables. Results of the research: The correlation between costs and taxes is negative as expected, as well as their relationship with the liquidity. Contrary to the expectations, the correlation between taxes and costs is mostly positive, alike the relationship between liquidity and debt. Findings are characteristic for the Polish market that is rather conservative in the approach to taxes, liquidity and leverage strategies compared to other developed markets. These findings prove that liquidity and debt management issues are subjective and related to the market behavior such as tax evasion attitudes.